2019
DOI: 10.1186/s12986-019-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat reduction is positively associated with blood pressure reduction in overweight or obese males but not females: an observational study

Abstract: Background Visceral adiposity has been reported to play a key role in hypertension compared with other measurements of regional or general obesity. The aim of current study was to evaluate the relationship between visceral fat reduction and changes in blood pressure in a group of overweight or obese Chinese individuals. Methods An observational study was conducted with 168 participants (ChiCTR-OOC-17012000). Body composition, blood parameters and blood pressure were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In addition, we found that high VF was linked to a higher likelihood of having hypertension. Visceral adiposity has been proven to be associated with higher blood pressure ( 64 – 66 ). The relationship between visceral fat and hypertension was also documented in other studies ( 36 , 60 , 67 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that high VF was linked to a higher likelihood of having hypertension. Visceral adiposity has been proven to be associated with higher blood pressure ( 64 – 66 ). The relationship between visceral fat and hypertension was also documented in other studies ( 36 , 60 , 67 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, a positive association was observed between reduction in body visceral fat and improvements in both SBP and DBP in males in a 12-week meal replacement intervention. [ 18 ] Fox et al . also observed that body visceral fat significantly correlated ( P < 0.001) with SBP and DBP[ 19 ] among Americans.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome will be assessed with multi-frequency bioelectrical impedance analysis with 8-point tactile electrodes (InBody 720; Biospace, Seoul, Korea) [ 21 ]. Bioelectrical impedance will be measured within 2 min, standing on bare foot and grasping the hand electrodes with arms in the vertical position as is described in an article of our team [ 22 ]. Body composition will be measured at baseline, day 45 and day 90.…”
Section: Methodsmentioning
confidence: 99%